Bioinspired Anti‐Fogging and Anti‐Fouling Artificial Compound Eyes. Issue 17 (12th July 2022) - Li, Minjing; Yang, Tongzhen; Yang, Qing; Fang, Zheng; Bian, Hao; Zhang, Chengjun; Hou, Xun; Chen, Feng
Abstract: Curved artificial compound eyes (ACEs) attract enormous research interest owing to their potential applications in medical devices, surveillance imaging, target tracking, and so on. However, fog, dust, or other liquids are likely to condense on the device surface under a humid, low‐temperature environment or outdoors, thus affecting the optical performance. In this work, a multi‐functional ACE (MF‐ACE) is fabricated by a combination of i) femtosecond laser wet etching, ii) soft lithography, and iii) polydimethylsiloxane (PDMS) swelling methods. The fabricated device is close‐packed with over 3000 microlenses (≈108 µm diameter and ≈15 µm height) on a spherical macrolens (6.56 cm diameter and 0.87 cm height). The trapped silicone oil in the cross‐linked PDMS endows the as‐fabricated ACE with excellent water repellence and anti‐fogging, anti‐fouling, and self‐cleaning abilities. In addition, the ACE shows high optical performance and the ommatidia have a spatial resolution of 50.8 lp mm −1 . The imaging and focusing experiments demonstrate its high optical properties and uniformity. It is anticipated that this research may provide useful guidelines for the fabrication of anti‐fogging and anti‐fouling optical devices, and such device enables potential applications in autonomous vehicles, medical, or vision systems under harsh environmental conditions. Abstract : An anti‐fogging and anti‐fouling artificial compound eye is prepared by the combination of femtosecond laser wet etching, soft lithography, and PDMS swelling methods. The resultant ACE component integrates more than 3000 high‐quality ommatidia over its large viewing angle. The trapped silicone oil endows the device with a great anti‐fogging ability and excellent liquid‐repellent capacity.